Antioxidant profiling of native and modified cereal brans. (3rd December 2018) - Ahmad, Farah; Pasha, Imran; Saeed, Muhammad; Asgher, Muhammad
Summary: Bran is detached from cereals during roller‐milling operations and considered as a byproduct of milling. Bran carries phenolics and antioxidants in appreciable quantities which can be heightened by modification. In the present project, four cereals were under study that is, wheat, barley, millet and sorghum. Bran was separated from cereal grains and was subjected to size reduction that is, fine (1 mm) and coarse (2 mm) and enzymatic modification by using xylanase and cellulase. Total phenolic content (TPC), total flavonoids content (TFC) and phytic acid were determined spectrophotometrically and phenolic acids through HPLC. TPC and TFC were recorded highest in xylanase‐treated millet bran (0.304 mg GAE g −1 and 211.42 μg g −1 QE respectively). In vitro antioxidant activity assessed by DPPH and FRAP was found to be highest in coarse millet bran (89.51% inhibition) and native sorghum bran (722.52 μMFeSO4 g −1 ) respectively. Phytic acid was observed highest in xylanase‐treated barley bran (5.80 g per 100 g). Abstract : Brans from cereals including wheat, barley, millet and sorghum were separated through milling and termed as native brans. The native brans were further ground to two sizes as fine (1 mm) and coarse (2 mm) and enzymatically modified using xylanase and cellulase. All the brans were assessed for phenolics profile and antioxidant activities.